Preparation and transfer of Burkholderia mallei production strain 5584 in accordance with the biosafety requirements - E. A. Artemeva; L. A. Melnikova; A. P. Rodionov (Ветеринария сегодня)
The Veterinary Service of the Russian Federation takes measures to ensure regular control of livestock health status, to prevent infectious diseases and their introduction into the country; and if such diseases are diagnosed, it takes measures to prevent their spread and contain outbreaks as soon as possible. Success of the taken measures depends on the use of various diagnostic, preventive and therapeutic drugs. In order to produce such medicinal products, biofactories use production and reference strains with stable biological properties, which are stored in national collections of microorganisms. The only keeper of glanders strains is the Laboratory for Collection of Strains of Microorganisms in the FSBSI «FCTRBS-ARRVI», subordinated to the Ministry of Agriculture of the Russian Federation. The following steps were taken due to the official request from FKP Kursk Biofactory – BIOK Company for the transfer of Burkholderia mallei production strain 5584 from the collection of the institution: the strain was passaged in golden hamsters, its viability was determined and biological properties of the culture were studied. The strain was transferred in accordance with the established procedure and in compliance with the biosafety requirements. As the work progressed, Burkholderia mallei strain 5584 culture was isolated and freeze-dried. Before the transfer, biological properties of the freeze-dried Burkholderia mallei strain 5584 were studied for their compliance with the passport data. The obtained results showed that the Laboratory for Collection of Strains of Microorganisms in the FSBSI «FCTRBS-ARRVI» provides optimal conditions to preserve the strain viability and initial biological properties after 5 years of storage. Analysis of the data obtained during the transfer of Burkholderia mallei strain 5584 allowed us to assess the actions taken at all stages of the procedure. It was established that the transfer procedure for the requested glanders production strain complied with the biosafety requirements and regulatory framework regulating the process.